Low back pain among hospital workers in Kano, North-west Nigeria - MK Abubakar; A Rabiu; MU Ibrahim; KA Musa; S Muhammad; AA Mamuda (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: About 90% of individuals will experience back pain at one point or the other in their lives. Hospital workers are considered to have a considerable risk of developing low back pain. Objective: To determine the prevalence and risk factors for low back pain among health workers in tertiary hospitals in Kano, Nigeria. Methods: The study was a cross-sectional survey. A questionnaire was designed and administered to 200 personnel of the teaching hospitals in Kano. Socio-demographic characteristics, presence of low back pain, factors that relieve and aggravate the low back pain and relationship of back pain and work activities, were recorded on the questionnaire. Results: The mean age of the respondents was 33.4±7.08 years. Sixty-six per cent of the respondents had back pain within a year of the study. There was a 29% point prevalence of low back pain among the respondents. Statistically significant association was established between various activities such as prolonged sitting and walking and pain in the lower back (p = 0.000). There was an association between low back pain and the type of job (department) of the respondents (p = 0.016). The dull ache was the predominant presentation (58%) followed by piercing and gripping in 20% and 19% respectively. Prolonged sitting was the main aggravating factor, while numbness was the main feature of referral in 18%. Only 5.0% of the respondents used medications for their back pain. Conclusion: Low back pain is common among hospital workers with a point prevalence of 29.1%. About 25% had low back pains that prevented participated in normal duty. Majority of the respondents believed back pain is preventable.